Photoconducting properties of Cd0.4ZnO0.6/p-Si photodiode by sol gel method - Tataroglu, A.; Aydin, H.; Al-Ghamdi, Ahmed A.; El-Tantawy, Farid; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Springer, 2014)
Al/Cd0.4ZnO0.6/p-Si Schottky photodiode was successfully fabricated via sol-gel process. The current-voltage characteristics of the diode were performed in dark and illumination conditions. The electronic parameters of the diode were determined using the thermionic emission theory. The values of ideality factor (n) and barrier height (I broken vertical bar(B0)) values of the diode were found to be about 5.80 and 0.80 eV, respectively. The photocurrent results in the reverse bias of the diode indicate that the current under illumination is higher than the dark current. The capacitance-voltage (C-V) and conductance-voltage (G-V) measurements of the diode were carried out in the range of 50 kHz-1 MHz. The observed decrease in the capacitance and increase in the conductance with the increasing frequency were explained on the basis of interface states. The obtained results indicate that Cd0.4ZnO0.6/p-Si junction is a Schottky type photodiode.
Keywords: Schottky diode; Photodiode; CdZnO film